Dark Matter With Stückelberg Axions - Corianò, Claudio; Frampton, Paul H.; Irges, Nikos; Tatullo, Alessandro (Frontiers in Physics, 2019)
We review a class of models which generalize the traditional Peccei-Quinn (PQ) axion solution by a Stückelberg psedudoscalar. Such axion models represent a significant variant respect to those scenarios where axion fields are associated with global anomalies, being a Stückelberg field, essential for the cancellation of gauge anomalies in the presence of extra U(1) symmetries. The extra neutral currents associated with these models have been investigated in the past in orientifold models with intersecting branes, under the assumption that the Stückelberg scale was in the multi-TeV region. Such constructions, at the field theory level, are quite general and can be interpreted as the four-dimensional field theory realization of the Green-Schwarz mechanism of anomaly cancellation of string theory. We present an overview of models of this type in the TeV/multi TeV range in their original formulation and their recent embeddings into an ordinary GUT theory, presenting an E_6× U(1)_X model as an example. In this case the model contains two axions, the first corresponding to a Peccei-Quinn axion, whose misalignment takes place at the QCD phase transition, with a mass in the milli-eV region and which solves the strong CP problem. The second axion is ultralight, in the 10^-18-10^-22 eV region, due to a misalignment and a decoupling taking place at the GUT scale. The two scales introduced by the PQ solution, the PQ breaking scale and the misalignment scale at the QCD hadron transition, become the Planck and the GUT scales respectively, with a global anomaly replaced by a gauge anomaly. The periodic potential and the corresponding oscillations are related to a particle whose De Broglie wavelength can reach 10 kpc. Such a sub-galactic scale has been deemed necessary in order to resolve several dark matter issues at the astrophysical level.